Potential use of CNTs for production of zero thermal expansion coefficient composite materials: An experimental evaluation of axial thermal expansion coefficient of CNTs using a combination of thermal expansion and uniaxial tensile tests. (April 2017) - Shirasu, Keiichi; Nakamura, Akihiro; Yamamoto, Go; Ogasawara, Toshio; Shimamura, Yoshinobu; Inoue, Yoku; Hashida, Toshiyuki
Abstract: Feasibility of using multi-walled carbon nanotubes (MWCNTs) for the control of coefficients of thermal expansion (CTEs) of composite materials was evaluated, based on experimental data of CTEs and Young's modulus newly obtained using a combined testing procedure. The axial CTE of the MWCNTs were evaluated over the temperature range −5 °C to 85 °C by using the MWCNT's Young's modulus and CTE of the aligned MWCNT reinforced epoxy composites in Turner's model. The Young's moduli of the MWCNTs were calculated by using Voigt model and the composite Young's modulus measured by tensile tests. The MWCNTs were shown to possess negative CTEs, and the nanotube CTEs tended to become less negative with increasing temperature. Owing to their large Young's modulus, aspect ratio and negative CTEs, the use of MWCNTs aligned axially was shown to be effective at controlling the CTE of polymer composites at lower volume fractions compared to conventional negative CTE materials.